Micro/Nanofluidic‐Enabled Biomedical Devices: Integration of Structural Design and Manufacturing. Issue 4 (28th December 2021) - Yin, Mengtian; Alexander Kim, Zachary; Xu, Baoxing
Abstract : Micro/nanofluidic devices and systems have attracted ever‐growing attention in healthcare applications over the past decades due to low‐cost yet easy‐customizable functions with the demand of only a small volume of sample fluid. The continuous development, in particular, supported by the emergence of new materials, capable of meeting critical needs in next‐generation, wearable, and multifunctional biomedical devices for at‐home, personalized healthcare monitoring, is challenging the principles and strategies of structural design, manufacturing, and their seamless integration. This review summarizes the progress in micro/nanofluidic‐enabled biomedical devices with a focus on structural design, manufacturing, and applications in healthcare. Structures of fluidic channels and liquid actuation strength are given to elucidate the manipulations and controls of fluid transports that help capture desirable information of interest, including component separation, extraction, measurements, and disease diagnoses. Manufacturing processes of fluidic devices in micro‐ and nanoscales and their basic working principles are also presented, ranging from lithography in traditional hard materials to 3D printing in emerging soft materials. The selected examples and demonstrations are illustrated to highlight applications of biomedical fluidic devices in a broad variety of disease detection and diagnosis. The associated challenges and future opportunities are discussed. Abstract : Micro/nanofluidic devices and systems that allow to sense transported liquid offer an attractive platform in biomedical engineering and healthcare monitoring. The concepts and strategies of design and manufacturing that are crucial to achieve low‐cost and user‐friendly features of the devices and systems with multifunctionalities, together with the associated challenges and opportunities, are discussed with representative biomedical applications.